Use of complementary therapies and non-prescribed medication in patients with Parkinson's disease. Issue 924 (1st October 2002) - Ferry, P; Johnson, M; Wallis, P
Abstract : Patients with Parkinson's disease resort to complementary therapy and non-prescribed medication in the hope of improving their quality of life. In the US 40% of patients with Parkinson's disease reported the use of at least one form of complementary therapy for Parkinson's disease. Data for the UK are limited. A structured questionnaire was administered to consecutive patients attending a Parkinson's disease clinic. Patients were excluded if they were cognitively impaired, if they were living in an institution, or if they declined to take part. The participants were asked about current and previous use of complementary therapy in general and Parkinson's disease in particular and were presented with an extensive list of complementary therapies and non-prescribed medications. The response rate was 90% and 80 patients met the inclusion criteria. Fifty four per cent (n=44) reported the use of at least one form of complementary therapy or non-prescribed medication either for Parkinson's disease or for some other indication, of whom 31 (38.7% of the total sample) used it solely for the treatment of Parkinson's disease. The most commonly used complementary therapies for Parkinson's disease were massage (n=9) and aromatherapy (n=8). Non-prescribed medication was mainly used for indications other than Parkinson's disease and the commonest drugs used were simple analgesics (n=7), cod liver oil (n=5), and multivitamins (n=4). The use of complementary therapy for Parkinson's disease correlated significantly (Pearson's r =0.44, p=0.01) with a younger age at diagnosis of Parkinson's disease. Comorbidity correlated significantly with complementary therapy use for indications other than Parkinson's disease (Pearson's r =0.29, p= 0.01). The use of complementary therapy for Parkinson's disease in this UK based clinic closely mimics that in the US. Non-pharmacological complementary therapy is mainly used for Parkinson's disease, while non-prescribed medication is more commonly used for other indications.